Overcoming apathy in research on organophosphate poisoning. Issue 7476 (18th November 2004) - Buckley, Nick A; Roberts, Darren; Eddleston, Michael
Abstract : High rates of pesticide poisoning in developing countries and increasing risk of nerve gas attacks in the West mean effective antidotes for organophosphates should be a worldwide priority